2013
DOI: 10.1017/s0031182013001340
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity ofEchinococcusspp. in Russia

Abstract: In Russia, both alveolar and cystic echinococcoses are endemic. This study aimed to identify the aetiological agents of the diseases and to investigate the distribution of each Echinococcus species in Russia. A total of 75 Echinococcus specimens were collected from 14 host species from 2010 to 2012. Based on the mitochondrial DNA sequences, they were identified as Echinococcus granulosus sensu stricto (s.s.), E. canadensis and E. multilocularis. E. granulosus s.s. was confirmed in the European Russia and the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 42 publications
1
92
0
3
Order By: Relevance
“…Due to its high discriminative power, EmsB has been primarily used for the study of local diversity in Europe (Knapp et al, 2008). Our present understanding of the global genetic structure of the parasite has been initially established using concatenated sequences of the mitochondrial cob, nad2 and cox1 genes Gesy et al, 2013), as well as by using cox1 sequences alone (Konyaev et al, 2012a(Konyaev et al, , 2013. Initially, haplotypes of mt DNA sequences were thought to cluster in correlation with geographical regions, forming 'European', 'Asian', 'Mongolian' and 'North American' clades ).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its high discriminative power, EmsB has been primarily used for the study of local diversity in Europe (Knapp et al, 2008). Our present understanding of the global genetic structure of the parasite has been initially established using concatenated sequences of the mitochondrial cob, nad2 and cox1 genes Gesy et al, 2013), as well as by using cox1 sequences alone (Konyaev et al, 2012a(Konyaev et al, , 2013. Initially, haplotypes of mt DNA sequences were thought to cluster in correlation with geographical regions, forming 'European', 'Asian', 'Mongolian' and 'North American' clades ).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Initially, haplotypes of mt DNA sequences were thought to cluster in correlation with geographical regions, forming 'European', 'Asian', 'Mongolian' and 'North American' clades ). More recent data, still limited by inadequate geographical and numerical sampling coverage, demonstrate that variants of the 'European' clade are widespread at least in western Canada Massolo et al, 2014;Gesy and Jenkins, 2015), 'Asian' haplotypes are reported in western Russia and St. Lawrence Island, Alaska, and isolates clustering most closely with the North American (Alaskan) N1 genotype were found in arctic parts of Siberia (Konyaev et al, 2013); Svalbard, Norway (Knapp et al, 2012) and St. Lawrence Island, Alaska (Table 1). The diversity of E. multilocularis in the circumpolar North is recently reviewed in (Davidson et al, 2016).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…For the PCR-negative fecal samples, precipitation with ethanol was used to eliminate false negatives and increase sensitivity, as could be seen when the detection increased from 0 % to 89 % in the case of E. shiquicus coproDNA using samples from fox with an autopsy positive for echinococcosis (Boufana et al). Konyaev et al (2013), of the Institute of Animal Ecology in Novosibirsk, Russia, studied a total of 75 samples of Echinococcus in European Russia and the Altai region between 2010 and 2012, finding the G6, G8 and G10 genotypes. In addition, 4 genotypes of E. multilocularis were identified (Konyaev et al).…”
Section: Available Evidencementioning
confidence: 99%
“…It also requires us to identify the parasite species Konyaev et al 2013;Said Ali et al 2013;Sako et al 2013). This can be effected by integrating human and animal epidemiology with host behaviour and parasite ecology .…”
Section: )mentioning
confidence: 99%
“…McManus (2013) overviews some historical observations on the biology and taxonomy of Echinococcus. Nakao et al (2013) consider the taxonomic status of E. canadensis, and Konyaev et al (2013) report recent data on Echinococcus spp. in Russia and describe, for the first time, different genotypes of E. multilocularis and E. canadensis, G6, G7 and G10 in that country.…”
mentioning
confidence: 99%